Analisis Pengaruh Struktur Modal Dewan Komisaris Kepemilikan Institusional Kebijakan Dividen Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Tivitasari, Niki, Drs.Wiyadi, M.M,Ph.D (2017)
This study aims to examine empirically the effect of capital structure, board size, institutional ownership, development policy and the size of the company's dividends to corporate value. This study uses secondary data derived from the Indonesia Stock Exchange website and the Indonesian Capital Market Directory (ICMD). The study population was Pharma companies listed in Indonesia Stock Exchange from 2006 to 2015. The research sample was determined by purposive sampling. Data analysis was performed using linear regression. The results showed that the coefficient of determination obtained 0.501 which means a 50.1% value of the company was affected by the capital structure, the board of commissioners, institutional ownership, dividend policy and the size of the company and the remaining 49.9% is influenced by variables outside the model. Partially, the results showed that the capital structure and institutional ownership has a significant effect on the value of the company, while the board size, and the size of the company's dividend policy does not affect the value of the company.